Indonesia's Role in Protecting High Seas Biodiversity: Challenges and Opportunities in Light of the Biodiversity Beyond National Jurisdiction Treaty - Wati, Erna (Jurnal Hukum IUS QUIA IUSTUM, 2025)
This research paper is a product of a doctrinal legal study that examines Indonesia's role in addressing challenges and opportunities related to marine biodiversity protection in international waters. As a leading maritime nation, Indonesia plays a crucial role in global efforts to protect ocean health, especially in the face of increasing threats such as overfishing, pollution, and climate change. These issues are regulated in international legal frameworks such as the United Nations Convention on the Law of the Sea (UNCLOS) and the Biodiversity Beyond National Jurisdiction (BBNJ) Treaty of 2023. By using a normative legal study approach, this study analyses international treaties, conventions, and academic literature to evaluate the application of the "Common Concern of Humankind" (CCH) doctrine in addressing biodiversity decline. Recognizing the degradation of high seas as CCH is essential to establishing an inclusive and effective legal framework, as it emphasizes shared global responsibilities in improving ocean governance. Leveraging its strategic position, Indonesia actively promotes the CCH principle through participation in BBNJ negotiations and regional initiatives such as the AIS Forum. While challenges remain, particularly in balancing economic interests with conservation efforts, Indonesia’s unyielding commitment and leadership continue to push for sustainable ocean governance and high seas conservation.Keywords: BBNJ Agreement, Common Concern of Humankind, Marine Biodiversity, Sustainable Ocean Management. AbstrakArtikel penelitian ini merupakan penelitian hukum doktrinal yang mengkaji peran Indonesia dalam menghadapi tantangan dan peluang terkait perlindungan keanekaragaman hayati laut di perairan internasional. Sebagai negara maritim terkemuka, Indonesia berperan penting dalam upaya global untuk melindungi kesehatan laut, terutama menghadapi ancaman yang semakin meningkat seperti penangkapan ikan berlebih, polusi, dan perubahan iklim. Isu-isu ini diatur dalam kerangka hukum internasional seperti Konvensi Perserikatan Bangsa-Bangsa tentang Hukum Laut (UNCLOS) dan Perjanjian Keanekaragaman Hayati di Luar Yurisdiksi Nasional (BBNJ) 2023. Dengan pendekatan kajian hukum normatif, penelitian ini menganalisis perjanjian internasional, konvensi, dan literatur akademik untuk mengevaluasi penerapan doktrin "Kepedulian Bersama bagi Umat Manusia" (Common Concern of Humankind/CCH) dalam mengatasi penurunan keanekaragaman hayati. Mengakui degradasi laut lepas sebagai CCH penting untuk membentuk kerangka hukum yang inklusif dan efektif, karena hal ini menekankan tanggung jawab bersama secara global dalam meningkatkan tata kelola laut. Dengan memanfaatkan posisinya yang strategis, Indonesia secara aktif mempromosikan prinsip CCH melalui partisipasi dalam negosiasi BBNJ dan inisiatif regional seperti Forum AIS. Meski tantangan tetap ada, terutama dalam menyeimbangkan kepentingan ekonomi dengan upaya konservasi, komitmen kuat dan kepemimpinan Indonesia terus mendorong tata kelola laut yang berkelanjutan dan pelestarian laut lepas.Kata kunci: Common Concern of Humankind, Keanekaragaman Hayati Laut, Pengelolaan Laut Berkelanjutan, Perjanjian BBNJ.